Cyclicality of bank liquidity creation - Denis Davydov; Zuzana Fungáčová; Laurent Weill (Bank of Finland, Institute for Economies in Transition (BOFIT), 2017)
This paper investigates the cyclicality of bank liquidity creation. Since liquidity creation is a major economic function of banks, their liquidity creation behavior may amplify business cycle fluctuations. Using the methodology of Berger and Bouwman (2009) to compute liquidity creation measures, we analyze the relation between GDP growth and liquidity creation of Russian banks from 2004 to 2015. Detailed quarterly data on a very large sample of banks and coexistence of different bank ownership types (state-owned, domestic private and foreign banks), makes Russia an ideal natural laboratory for study of cyclicality of liquidity creation for banks. We find that liquidity creation of banks is procyclical. We show that the liquidity creation behavior of state-owned banks and foreign banks is similar to that of domestic private banks in terms of procyclicality. We further find that the magnitude of procyclicality is higher for liquidity creation than for lending. Thus, while ownership of banks does not influence the liquidity creation behavior of banks, such behavior can amplify business cycle fluctuations.
URN:NBN:fi:bof-201703101183
Keywords: G21; 330